1999
DOI: 10.1097/00005176-199904000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Survival in Extrahepatic Biliary Atresia by Hepatic Duplex Sonography

Abstract: In children with extrahepatic biliary atresia, Doppler sonography of the hepatic blood flow is a noninvasive indicator of disease severity. Moreover, it allows a highly accurate prediction of patient survival for the following 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, hepatic artery branches nourish bile ducts, veins, and even nerves, and an arteriopathy of this kind may have profound influences in the liver morphology and functioning. This arteriopathy may explain the findings of Kardoff et al [8] and Broide et al [9] who detected increased arterial resistance in the hepatic arteries of BA patients with worse postportoenterostomy prognosis.…”
Section: Discussionmentioning
confidence: 74%
“…However, hepatic artery branches nourish bile ducts, veins, and even nerves, and an arteriopathy of this kind may have profound influences in the liver morphology and functioning. This arteriopathy may explain the findings of Kardoff et al [8] and Broide et al [9] who detected increased arterial resistance in the hepatic arteries of BA patients with worse postportoenterostomy prognosis.…”
Section: Discussionmentioning
confidence: 74%
“…Searches of the bibliographies of these articles identified no additional eligible studies. Of these 49 articles, 32 were further excluded after reviewing the full text: 13 studies that were not in the field of interest (6 studies that only included minor sonographic features, 4 studies that were associated with surgery, 2 studies that were related to choledochal cysts, and 1 study that included clinical findings of biliary atresia), 11 studies with a partially overlapping patient cohort, 5 studies with insufficient data to construct a diagnostic 2 × 2 table, 1 study with nonconsecutive patients, 1 study that included only infants younger than 90 days, and 1 non‐English article . Finally, 17 eligible studies, which included a total sample size of 1444 patients, were finally included in our meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…Available data for Doppler sonography in children with chronic liver disorders indicate lower portal flow velocities and higher hepatic arterial resistance indices than those in healthy control subjects [9,10]. It has been reported that there is a significant difference in portal venous velocity between Child-Pugh A class, and Child-Pugh B and C classes of liver cirrhosis in patients with biliary atresia [11].…”
Section: Discussionmentioning
confidence: 99%